Gambaran Penggunaan KB IUD (Intra Uterine Device) Pada Ibu Pasca Melahirkan Di Puskesmas Medan Deli - Anggi Permatasari Sidabutar, Rasmina; Ema Mahrani (2025)
Post-coital contraception is an important strategy in family planning to prevent unplanned pregnancies and optimize maternal and child health. One of the recommended contraceptive methods is the Intrauterine Device (IUD), which can be inserted immediately after delivery. However, the adoption rate of post-sync IUD is still low in many areas, including in Medan Deli Community Health Center. This study aims to describe the use of the post-sync IUD and analyze the factors that influence its adoption, including maternal motivation and partner support. This study used a descriptive design with a cross-sectional approach. The study population was postpartum mothers who used the IUD at Puskesmas Medan Deli with a total of 35 respondents selected through total sampling technique. Data were collected using a structured questionnaire and analyzed by descriptive statistics using SPSS. Most respondents were 35-40 years old (43%), had a high school education level (51%), and were housewives (54%). Motivation to use the IUD post-saline was high (57%), while 43% were in the moderate category. Husband support for IUD use was low, with 66% of respondents reporting a lack of spousal support. Despite the high motivation of women to use the IUD post-sync, there are still significant barriers to implementation, especially from social factors such as spousal support. Therefore, there is a need to educate women about the importance of IUD use.